Strategi Komunikasi Al-Ittihadiyah Sumatera Utara dalam Mengembangkan Dakwah di Sumatera Utara - Rahmi Fitra Ulwani; Mailin Mailin; Zainun Zainun (UNIVERSITAS SARI MUTIARA INDONESIA, 2021)
This study aims to identify, analyze and describe Al-Ittihadiyah's communication strategy in developing the Da'wah Program in North Sumatra. In this research, there are Al-Ittihadiyah communication strategies, da'wah programs and the obstacles and successes that have been carried out by Al-Ittihadiyah North Sumatra. This study uses a qualitative method with the type of field research that describes the results of research objectively to the conditions and characteristics encountered in the field. Data collection techniques in this study using observation, interviews and documentation. The data analysis of this research used data reduction, data presentation, and conclusion drawing. The validity of the data collected is checked. The results of this study are the communication strategies carried out by Al-Ittihadiyah North Sumatra in developing a da'wah program using 5 communication strategies, namely; wisdom communication strategy, communication strategy mau'izhatul hasanah, communication strategy by mahabbah, top-down communication, bottom-up communication. North Sumatra Al-Ittihadiyah da'wah programs aimed at the benefit of the community consist of 4 parts, namely programs in the field of da'wah, programs in education, programs in the social sector and programs in the field of public economy, each of which has many activities. Obstacles that occur when developing a da'wah program are divided into two parts, namely internal and external, internal factors, namely lack of funding and lack of communication and time sharing because the board of Al-Ittihadiyah each has a job, and external factors, namely the conditions of the community faced and the lack of people who know about this organization even though this organization is an original organization founded in North Sumatra. The success of the da'wah program achieved by Al-Ittihadiyah North Sumatra is also very satisfying, seen from the large number of people in minority areas who have converted to Islam and are still being nurtured until now, many people are aware of this organization, ongoing training, schools that are continuously being built and already has its own university and other Islamic development center developments.